(untitled) (Journal of Science and Technology, 2016)
A large number of low-income households in Kumasi, in the Ashanti Region, live in compound houses. The earlier compound houses built in mud are mostly single-storey but this has gradually metamorphosed, over the years, into multi-storey compound houses within the urban areas. This has been attributed mainly to the high land values and efforts by landlords to maximize the use of land, thereby absorbing the large number of urban poor who lack accommodation. The incidence of a large number of rooms with this kind of design enable cost of renting a room to be cheaper and thus accessible to the poor. This paper seeks to present the merits and demerits of the compound house through studies conducted by the Department of Architecture, from 1985 to 2005, as well as employing an “archito-centric” approach to solving some of the problems, especially the preparation of fufu on upper floors of the building, washing and drying of laundry, refuse disposal, cooking, circulation and storage.